Effects of group work on reading comprehension and reading motivation of tertiary level ESL learners - Turiman, Syamimi (2012)
The present study investigated the effects of group work on English as a Second Language (ESL) undergraduates’ reading comprehension and motivation to read. Four research questions which guided this study were as follows: 1) Is there any significant difference in ESL students’ reading comprehension performance between those who are in the teacher-fronted instruction compared to those working in groups? 2) Is group work more effective than teacher-fronted instruction in improving different levels of comprehension? 3) Is there any significant difference in ESL students’ reading motivation between those in the control and experimental groups? 4) What are the students’ attitude towards group work in the reading classroom? A non-randomised control group pretest-posttest design was employed. Fifty eight students were divided into two groups; one worked in groups while the other experienced teacher-fronted technique. Four research instruments were used for data collection. A reading comprehension test from the Malaysian University English Test (MUET) Paper 3 was administered to the participants before and after the treatment ends. Also, all of the participants completed an L2 reading motivation questionnaire in another session after the post-test. An Attitude Towards Group Work questionnaire was administered only to the participants in the experimental group. Six students from the experimental group were interviewed. The participants in the experimental group were assigned reading tasks and they had to work in groups during the while-reading and post-reading stages while participants in the control group deal with the same reading tasks and work it out individually. Results showed that the post-test mean score and the overall mean score of the experimental group was significantly higher than that of the control group for both reading comprehension test and reading motivation questionnaire. A statistically significant difference between the Experimental and Control group was reported on the inferential comprehension in Barrett Taxonomy. There were significant differences in three factors of reading motivation between both groups. Findings from the questionnaire and the semi-structured interview indicate overall positive attitudes towards group work in reading classroom. The study concluded that group work is seen as a more effective method over teacherfronted technique, to increase students’ comprehension of L2 texts, and to increase their motivation to read. A number of implications have been drawn regarding the inclusion of group work in the ESL reading classroom.